Investigation of Extraoral Dental Radiography Examination Rejections at a Dental and Oral Hospital in Semarang, Indonesia - Dina Rusydiana; Dona Doni Setyawan (Dental and Oral Hospital of Universitas Muhammadiyah Semarang, 2023)
Background : Extraoral radiography techniques, such as panoramic radiography and cephalometric radiography, are used to obtain an overall view of the teeth, jaws, and surrounding tissues. However, there are instances where radiographic images are rejected or marked as inadequate based on the required quality standards. Reject analysis is a method of evaluation that involves analyzing rejected dental radiographic images. This research will identify the most common factors contributing to image rejection and provide recommendations for improving the quality of dental radiographic images Methode : The type of scientific study in this research is quantitative and descriptive. The research was conducted at the Radiodiagnostic Department of the Dental Hospital, Muhammadiyah University of Semarang. The total sample size taken was 301 extraoral radiographic films. The research data were obtained through a retrospective survey approach and observation method. The analysis was performed using Microsoft Excel 2021 application. Result : The primary factors contributing to film rejection are patient movement (50%), patient positioning (25%), and device settings (25%). Film rejection for extraoral radiographic examinations consisted of 2 films in Panoramic examinations, accounting for 50%, and 2 films in Cephalometric examinations, also accounting for 50% Conclusion : The film rejection ratio for extraoral dental radiography examinations conducted at the Radiodiagnostic Department of the Dental Hospital, Universitas Muhammadiyah Semarang, remained below the normal limit value of 1.29%.